Modification of whey−soybean mixed protein by sequential high-pressure homogenization and transglutaminase treatment. (30th December 2022) - Han, Xiue; Liang, Zhiqiang; Tian, Songfan; Liu, Lu; Wang, Song
Abstract: The main purpose of this paper was to investigate the effect of High-pressure homogenization (HPH) and sequential HPH−Transglutaminase (TGase) treatment on the structural, physicochemical, and functional characteristics of mixtures of whey protein isolate (WPI) and soy protein isolate (SPI). Compared with the untreated WPI-SPI mixture protein, the mean particle size of WPI-SPI pretreatment with HPH (H-WS) and TGase-induced H-WS were reduced by up to 62%. Circular dichroism spectroscopy, surface hydrophobicity, and intrinsic ﬂuorescence spectroscopy showed that HPH and sequential HPH−TGase treatment on WS increased in α-helix from 9% to 13%, decreased in β-sheet from 36% to 32%. The emulsification and foaming properties of the mixed protein were increased from 59 to 79 m 2 /g, 120%–158% respectively. Highlights: Whey protein isolate-soy protein isolate mixed system had been produced. The mixed protein system was treated with HPH or transglutaminase. The free sulfhydryl group and solubility of the treated complexes were increased. Interfacial properties of the complexes were increased by HPH or transglutaminase.